Revised Ordinances of the City of Danville, Illinois 179 (E. R. E. Kimbrough & W. J. Calhoun eds., 1892) - (:unkn) unknown (My University, 1883)
§ 23: Prohibited the carrying of a concealed pistol, revolver, derringer, Bowie knife, dirk, slungshot, metallic knuckles, or a razor, as a weapon, or any other deadly weapon. Also prohibited displaying the weapon in a threatening or boisterous manner. Punishable by fine of $1-100 and forfeiting the weapon, if ordered by the magistrate.
Keywords: BRANDISHING; CARRY - CONCEALED